2010
DOI: 10.1002/cphc.200900846
|View full text |Cite
|
Sign up to set email alerts
|

Coverage‐Dependent Self‐Assembly of Rubrene Molecules on Noble Metal Surfaces Observed by Scanning Tunneling Microscopy

Abstract: Coverage-dependent self-assembly of rubrene molecules on different noble metal surfaces, Au(111) and Au(100), Ag(111) and Ag(100), is presented. On Au(111), the homochiral supramolecular assemblies evolve with increasing rubrene coverage from very small structures composed of a few molecules, to honeycomb islets, and to one-dimensional chains of supramolecular pentamers. At higher coverage, the racemic mixture of molecules forms close-packed islands. On Au(100), chains of pentamers and two different types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 79 publications
3
34
2
Order By: Relevance
“…[22] However, recently, (sub)monolayers of rubrene on Au (111) are reported to formdepending on the specific preparation conditions-manifold supramolecular structures of essentially flat lying molecules as evidenced by scanning tunneling microscopy (STM). [23][24][25][26] Con sequently, the mutual supramolecular stabilization might lead to a conformational transition on a shorter length scale or even to the concomitant occurrence of rubrene in a twisted and a planar conformation in the monolayer on Au (111) or other inert substrates like graphite. In a recent STM study of rubrene on Bi (001) such a coexistence was actually experimentally shown for monolayer coverage.…”
Section: Doi: 101002/adma201103262mentioning
confidence: 99%
“…[22] However, recently, (sub)monolayers of rubrene on Au (111) are reported to formdepending on the specific preparation conditions-manifold supramolecular structures of essentially flat lying molecules as evidenced by scanning tunneling microscopy (STM). [23][24][25][26] Con sequently, the mutual supramolecular stabilization might lead to a conformational transition on a shorter length scale or even to the concomitant occurrence of rubrene in a twisted and a planar conformation in the monolayer on Au (111) or other inert substrates like graphite. In a recent STM study of rubrene on Bi (001) such a coexistence was actually experimentally shown for monolayer coverage.…”
Section: Doi: 101002/adma201103262mentioning
confidence: 99%
“…31 As a function of coverage, pentamers of rubrene were found to organize into a diffuse network of extended chains, in some cases coincident with the underlying Au(111) herringbone reconstruction. Higher coverage yielded the formation of close-packed islands.…”
Section: Introductionmentioning
confidence: 98%
“…Organization into network structures, rings or "bubbles," and stripe phases has been observed via scanning tunneling microscopy (STM) in numerous single and multicomponent molecular mixtures. [21][22][23][24][25][26][27][28][29][30][31][32][33] Self-organization can be engineered by controlling specific directional bonding motifs of the molecular components to guide assembly. [26][27][28][29][30] Self-assembly into complex molecular patterns can also be induced, as described above, by competing intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 3 previous study of monolayer rubrene on HOPG we showed that the main vibrational energy (determined in a single mode analysis of the vibrational fine structure of the UPS HOMO-derived peak) of the twisted conformation is slightly larger than that of the planar conformation 26 . The thin film structure and the conformation of rubrene on various substrates depend critically on the film thickness 37,[43][44][45] . Thus, in order to cover a thickness regime which is more relevant for device application, we explore the hole-phonon coupling beyond monolayer coverage in our combined angle-resolved UPS and metastable atom electron spectroscopy (MAES) study of vacuum-sublimed rubrene on HOPG Experimental section Rubrene (two times purified in high-vacuum) thin films were prepared by vacuum sublimation on clean HOPG surfaces using resistively heated quartz crucibles with deposition rates of about 0.25 Å/min as controlled by a quartz crystal microbalance.…”
Section: Introductionmentioning
confidence: 99%